INDIAN SCULPTURAL ART OF TRIVIKRAMA IMAGES FROM THE VAISNAVITE TEMPLES OF PRACHI VALLEY OF ODISHA, EASTERN INDIA - Abesha Shirko Lambebo, Ratnakar Mohapatra (International Journal of Advanced Science and Technology, 2020)
The worship of Lord Vishnu is very much popular among the Hindus of Odisha as well as India. Vamana (Trivikrama) is considered to be one of the ten avatars or incarnations of Lord Vishnu. Vaishnavism had deeply influenced the religious life of the people of Prachi Valley of Odisha in Eastern India. In fact, Prachi Valley is an important historical site of Odisha. The Trivikrama worship has been prevailing in the Prachi valley since the Ganga period of Odishan history. In Prachi valley, a good number of Trivikrama images are found to be worshipped as parsvadevatas in some Vaisnavite temples and in a few sites as presiding deity. The extant Trivikrama images of the Vaisnavite temples of Prachi Valley possess the iconographic features of the Odishan classical art of the medieval and early periods. The study of extant Trivikrama images of the Vaisnavite temples of Prachi Valley of Odisha is one of the fascinating aspects of the Indian sculptural art. From the artistic point of view, the Trivikrama images of the Vaisnavite temples of Prachi Valley are very interesting study for the scholars of art history. Really, the Prachi valley is an important centre of sculptural art of Odisha in Eastern India.